Electrical Properties of Self-Assembled Nano-Schottky Diodes. (28th September 2008) - Ruffino, F.; Canino, A.; Grimaldi, M. G.; Giannazzo, F.; Roccaforte, F.; Raineri, V.
Abstract : A bottom-up methodology to fabricate a nanostructured material by Au nanoclusters on 6H-SiC surface is illustrated. Furthermore, a methodology to control its structural properties by thermal-induced self-organization of the Au nanoclusters is demonstrated. To this aim, the self-organization kinetic mechanisms of Au nanoclusters on SiC surface were experimentally studied by scanning electron microscopy, atomic force microscopy, Rutherford backscattering spectrometry and theoretically modelled by a ripening process. The fabricated nanostructured materials were used to probe, by local conductive atomic force microscopy analyses, the electrical properties of nano-Schottky contact Au nanocluster/SiC. Strong efforts were dedicated to correlate the structural and electrical characteristics: the main observation was the Schottky barrier height dependence of the nano-Schottky contact on the cluster size. Such behavior was interpreted considering the physics of few electron quantum dots merged with the concepts of ballistic transport and thermoionic emission finding a satisfying agreement between the theoretical prediction and the experimental data. The fabricated Au nanocluster/SiC nanocontact is suggested as a prototype of nano-Schottky diode integrable in complex nanoelectronic circuits.